Pengembangan media pembelajaran fiqih berbasis game umo untuk meningkatkan hasil belajar peserta didik - Verayunita Siregar; Siti Halimah; Sakti Ritonga (SCHOULID: Indonesian Journal of School Counseling, 2025)
Globalization and the development of information and communication technology (ICT) have brought significant changes in the world of education. However, in learning certain subjects such as Fiqh, there are still challenges in increasing student interest and understanding due to less varied teaching methods and limited attractive learning media. This study aims to develop learning media based on Android educational games that integrate the Problem-Based Learning (PBL) approach to increase student engagement and understanding in learning Fiqh. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through interviews, observations, and questionnaires to measure the effectiveness of the developed media. The analysis was conducted qualitatively and quantitatively to assess aspects of student engagement, concept understanding, and learning experience. The results showed that the Android-based educational game developed was able to increase students' learning motivation and help them understand Fiqh material better. The application of the PBL approach in this game allows students to engage in active problem solving, thus improving critical thinking and problem solving skills. In addition, the integration of the Technological Pedagogical Content Knowledge (TPACK) model in the design of learning media maximizes students' learning motivation.